2021
DOI: 10.1111/cge.14007
|View full text |Cite
|
Sign up to set email alerts
|

Patients with acephalic spermatozoa syndrome linked to novel TSGA10/PMFBP1 variants have favorable pregnancy outcomes from intracytoplasmic sperm injection

Abstract: Acephalic spermatozoa syndrome is a rare form of teratozoospermia characterized by headless spermatozoa. Previous studies have found that variants in SUN5, PMFBP1, TSGA10, BRDT, and SPATC1L are associated with this phenotype. Many researchers have suggested that variants in TSGA10 without a proximal centriole might influence early embryonic development. This retrospective cohort study included 12 infertile men with severe acephalic spermatozoa in China. We identified six heterozygous variants and four homozygo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…22231), and all subjects signed informed consent forms. Human sperm smears were preserved in our laboratory [23] .…”
Section: Methodsmentioning
confidence: 99%
“…22231), and all subjects signed informed consent forms. Human sperm smears were preserved in our laboratory [23] .…”
Section: Methodsmentioning
confidence: 99%
“…SPATA6 is the first protein identified as a component of the HTCA using the knockout mouse model, and is crucial for the formation of the sperm HTCA (Yuan et al, 2015). Deficiencies in SUN5 (Elkhatib et al, 2017; Fang et al, 2018; Liu et al, 2020; Sha et al, 2018; Shang et al, 2018; Shang et al, 2017; Xiang et al, 2022; Zhang et al, 2021; Zhu et al, 2016) and PMFBP1 (Deng et al, 2022; Liu et al, 2020; Liu et al, 2021; Lu et al, 2021; Nie et al, 2022; Sha et al, 2019; Zhu et al, 2018) have been demonstrated to be associated with ASS in both humans and mice. The centriole-related protein, CENTLEIN, serves as a bona fide linker between SUN5 and PMFBP1 to participates in the HTCA assembly (Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%